2007
DOI: 10.1530/eje-07-0356
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in acromegalic subjects: data from AcroBel, the Belgian Registry on acromegaly

Abstract: Objective: To assess the impairment of quality of life (QoL), evaluated by the acromegaly QoL (AcroQoL) questionnaire, in patients with controlled and uncontrolled acromegaly. Design: Cross-sectional evaluation of AcroBel, a national observational registry of acromegalic patients newly diagnosed or in follow-up. Methods: Disease perception by the patients was evaluated by the disease-specific signs and symptoms score (SSS) and QoL was assessed by the AcroQoL questionnaire. Hormonal status was determined by cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 25 publications
11
41
4
1
Order By: Relevance
“…According to published studies men had better quality of life in some studies [4,16,19], whereas others show opposite results [5,20,21]. In our study younger patients had slightly higher quality of life scores, but again, these failed to reach statistical significance.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…According to published studies men had better quality of life in some studies [4,16,19], whereas others show opposite results [5,20,21]. In our study younger patients had slightly higher quality of life scores, but again, these failed to reach statistical significance.…”
Section: Resultscontrasting
confidence: 70%
“…In our study younger patients had slightly higher quality of life scores, but again, these failed to reach statistical significance. Previous studies showed that younger age was associated with better quality of life [14] and negative influence of age has been reported [5], whereas other studies have found no relationship [4,16,21,22]. In a recent Japanese study young age and previous radiotherapy were found to be associated with lower quality of life [23].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous analyses of the German pegvisomant observational study (16,17) have already given useful insights into the 'real-life' use of pegvisomant and assisted physicians with issues such as optimising dose titration (6). Several countries have organized national registries of patients with acromegaly, which contribute to gain insights on the actual conditions of diagnosis and treatment of this rare disease (10,11,18). The French Acromegaly Registry represents one such register that could be used to compare the profile of a general population of patients with acromegaly to the subset of patients treated with pegvisomant and included into ACROSTUDY.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between well-known complications and levels of GH and IGF1 are still a matter of debate. Along with increased risk for mortality and morbidity in acromegaly patients, non-biochemical parameters do not necessarily correlate with biochemical activity of acromegaly [34,35]. Correlations between levels of GH and IGF1 and motility parameters were not reported in previous acromegaly studies.…”
Section: Discussionmentioning
confidence: 99%